Isolation and Characterization of Methanobacterium thermoautotrophicum ΔH Mutants Unable To Grow under Hydrogen-Deprived Conditions - Pennings, Jeroen L. A. (American Society for Microbiology, 1998)
By using random mutagenesis and enrichment by chemostat culturing, we have developed mutants of Methanobacterium thermoautotrophicum that were unable to grow under hydrogen-deprived conditions. Physiological characterization showed that these mutants had poorer growth rates and growth yields than the wild-type strain. The mRNA levels of several key enzymes were lower than those in the wild-type strain. A fed-batch study showed that the expression levels were related to the hydrogen supply. In one mutant strain, expression of both methyl coenzyme M reductase isoenzyme I and coenzyme F(420)-dependent 5,10-methylenetetrahydromethanopterin dehydrogenase was impaired. The strain was also unable to form factor F(390), lending support to the hypothesis that the factor functions in regulation of methanogenesis in response to changes in the availability of hydrogen.